THE ROLE OF SENGON FORESTS IN CLIMATE-BASED AGROFESTRY IN BLITAR - Marti Winarni; Anang Susanto (International Journal of Multidisciplinary Reseach, 2026)
The condition of the land, as the main capital for farmers in their efforts to produce food, is greatly influenced by climate factors, namely rainfall, temperature, and humidity, which can be beneficial or detrimental. The purpose of this study was to determine the daily pattern of soil temperature and humidity at different depths under sengon-peanut stands. The importance of soil temperature and humidity data is that they can be used as input for agroforestry management. The study used a survey method, a specific location, and a specific time. This study was conducted in the KPH Blitar Forest, East Java. The study was conducted for three (3) months, starting from November 2022 to January 2023. The average soil humidity was 78.39% at a depth of 10 cm, 78.76% at a depth of 15 cm, 78.77% at a depth of 20 cm, and 79.28% at a depth of 25 cm. The average soil temperature at 25 cm is 28.89°C, at 10 cm it is 29.04°C, at 20 cm it is 28.94°C, and at 15 cm it is 29.01°C. Conversely, the deeper the soil, the higher the soil moisture tends to be.